Differences Among Types of Sexual Misconduct Incidents Reported to Title IX Coordinators and Institutional Stability in Incidents Over Time - Richards, Tara N. (Violence against women, 2024)
Sexual misconduct incidents reported to Title IX coordinators and stability in incident characteristics within institutions of higher education (IHEs) over time were examined. Data included two waves of reported incidents in 2016–2018 (n = 2,598) and 2018–2020 (n = 2,778) across Maryland IHEs (N = 40). Findings showed most reported incidents were for Other Sexual Misconduct (e.g., sexual harassment) versus Sexual Assault I (i.e., rape) or Sexual Assault II (e.g., unwanted sexual touching). Types of sexual misconduct differed regarding reporting by responsible employees, nonstudent perpetrators, and the range of accommodations accessed; institutional-level profiles of sexual misconduct were stable across waves. Implications and future research are discussed.